Formation of carbon nanotubes from potassium catalyzed pyrolysis of bituminous coal. (1st March 2019) - Zhang, Tiankai; Wang, Qi; Li, Guoqiang; Zhao, Yuqiong; Lv, Xuemei; Luo, Yunhuan; Zhang, Yongfa
Graphical abstract: Highlights: Directly synthesized the carbon nanotubes by potassium catalyzed pyrolysis of coal. Proposed a "stepwise" model to explain the growth mechanism of carbon nanotubes. Inferred the carbon source of nanotubes according to the coal's and coke's products. Abstract: In the present work, a novel method has been proposed, which can be used for generating carbon nanotubes (CNTs) using coal as the raw material and potassium hydroxide as the catalyst precursor. The results of Fourier Transform Infrared (FTIR) spectroscopy indicated that the groups of CH3, CH2 contained in the coal gradually disappeared during the potassium catalyzed pyrolysis. Raman analysis showed that the graphitization degree of catalytic pyrolysis products of raw coal was high, and the ratio of the intensities of G and D peaks (IG /ID ) was 3.0. The results of Scanning Electron Microscope (SEM) showed that there were many CNTs in the product. The Transmission Electron Microscopy (TEM) showed that these CNTs had different shapes (linear or curved) and have good graphite crystal structure with a wall number of 18–65 layers and a diameter of 20–155 nm. The potassium catalyst has the dual function of catalyzing the formation of CNTs and etching large molecular structure to generate carbon source. The formation process of CNTs is as follows: coal takes pyrolysis to produce small carbon-containing molecules such as CH4, and the small carbon-containing molecules formed CNTs through catalytic cracking under the action of catalyst. A "stepwise growth" model of CNTs was established.